Analisis Perhatian Guru PAK dalam Meningkatkan Rasa Percaya Diri Peserta Didik Kelas XI Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti SMK Negeri 1 Raya Kabupaten Simalungun Tahun Pembelajaran 2024/2025 - Lydia Nivea Indah Permatasari Silaban; Rusmauli Simbolon; Dorlan Naibaho; Hasudungan Simatupang; Andar Gunawan Pasaribu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The purpose of this study was to determine how to generate PAK teacher attention in increasing self-confidence in class XI students of SMK Negeri 1 Raya, Simalungun Regency, 2024/2025 Academic Year. The research method used is a qualitative method. The determination technique used to collect informants is using purposive sampling. The data collection technique used in this study used semi-structured interviews. The results of the study showed that the attention of PAK teachers in increasing the self-confidence of class XI students of SMK Negeri 1 Raya, namely: (1) PAK teachers have provided optimal attention by providing supervision, guidance, ideas and input. The supervision provided by PAK teachers is classified as very good with a percentage of 75%; (2) providing motivation to students. The motivation given by PAK teachers is classified as very good with a percentage of 85%; (3) some students lack self-confidence which is shown in an optimistic attitude but already have a responsible attitude which is classified as sufficient with a percentage of 43%; and (4) PAK teachers have used good communication with students which aims not to weaken students' self-confidence. PAK teacher communication is classified as good with a percentage of 80%.